Characterization of sodium hydroxide-treated kenaf fibres for biodegradable composite application - Hassan, Aziz; Isa, M.R. Mohd; Ishak, Zainal Arifin Mohd; Ishak, N.A.; Rahman, Normasmira Abd; Salleh, Fauzani Md (SAGE Publications, 2018)
Natural fibres have shown immense potential as reinforcement for composites in the place of conventional fibres. Natural fibres are lightweight, cheap and environmentally friendly. However, it is already established that natural fibres have poor interaction with polymers due to its hydrophilic nature, resulting in poor interfacial adhesion, which is detrimental to the properties of the composite. Chemical surface treatment has been done to improve the interfacial adhesion. Various concentrations of sodium hydroxide (NaOH) and soaking times were employed, and the treated fibres were then characterized using thermogravimetric analyser, X-ray powder diffraction and Fourier transform infrared (FTIR) spectrometer. Single-fibre tensile tests were done on selected samples. The surface of the fibre was analysed with field-emission scanning electron microscope to study the surface morphology of the treated and untreated fibres. Generally, the treated fibres have higher thermal stability compared to untreated fibres. However, no significant trend was observed as a result of varying NaOH concentration and soak time. It was also observed that kenaf fibres treated with 4% (w/v) NaOH for 5 h exhibited the highest tensile modulus and tensile strength compared to other treated fibres. Impact properties of composites prepared from untreated and NaOH-treated kenaf were tested to confirm the finding, and it was determined that the treated kenaf composites have superior impact properties to its untreated counterpart.